Active Surveillance, Drug Resistance, and Genotypic Profiling of Staphylococcus aureus Among School-Age Children in China - Liang, Bingshao; Liang, Xiaoyun; Gao, Fei; Long, Yan; Mai, Jialiang; Ai, Xiaolan; Wang, Jielin; Gao, Xiurong; Xiong, Zhile; Liang, Zhuwei; Zhang, Chao; Gong, Sitang; et al. (Frontiers in Medicine, 2021)
Methicillin-susceptible (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA) nasal colonization predisposes for endogenous infections and posed a major threat to children. Recently, cefoxitin/oxacillin-susceptible mecA-positive S. aureus (OS-MRSA) has been reported worldwide. Herein, a prospective, cross‑sectional study was conducted across five schools, representing three educational stages, in Guangzhou, China. Nasal swabs from 2,375 students were cultured for S. aureus and all isolates were subjected to antibiotic susceptibility testing phenotypically and confirmed by femB and mecA genetic detection, so that all the isolates were classified into MSSA, MRSA, or OS-MRSA. All the strains were also analyzed by multi-locus sequence typing. Among all 2,375 swabs obtained, S. aureus was detected in 744 children (31.3%, 95% CI: 25.9–36.7%), of whom 72 were MRSA (3.0%, 95% CI: 0.6–5.4%) and four were OS-MRSA (0.2%, 95% CI: 0.1–0.3%). The prevalence of S. aureus and MRSA was higher in younger children. The highest percentage of drug resistance of the S. aureus isolates (n = 744) was to penicillin (85.5%), followed by erythromycin (43.3%), clidamycin (41.0%). ST30, ST45, and ST188 were the most prevalent sequence types in MSSA, accounting for 38.7% of the total isolates, whereas ST45, ST59, and ST338 accounted for 74.6% of the MRSA isolates, and CC59 accounted for 75.0% of the OS-MRSA isolates. The MRSA and OS-MRSA isolates (n = 76) were grouped into three clades and one singleton. The top nine clonal complexes (CC30, CC45, CC5, CC1, CC15, CC944, CC398, CC59, CC7) represented 86.7% of all isolates. All the CC30 isolates were resistant to erythromycin and clidamycin, and almost all these isolates were also resistant to penicillin (99.2%). The CC45 and CC59 isolates exhibited high resistance rates to oxacillin at 31.5% and 59.0%, respectively. This study provides updated data that could be valuable for designing effective control strategies to mitigate the burden of disease and to improve the adequacy of empirical antimicrobial treatments for potentially harmful infections.